New Trends In The African Human Rights System: Prospects Of African Regional Human Rights Courts* (Global Journal of Human-Social Science, 2012)
One of the impacts of the Second World War WW II is the movement from the strict reliance on the principle of state sovereignty or v jurisdiction to the concept of universality 1 The concept gave impetus to and culminated in the adoption of plethora of human rights instruments Under the United Nations auspices the Universal Declaration of Human Rights was adopted in 1948 2 and today it represents a major milestone in human progress 3 It is also the corner stone of contemporary human rights law 4 O
Keywords: strict; domestic; universality